Dehydrative π-extension to nanographenes with zig-zag edges. Issue 1 (December 2018) - Lungerich, Dominik; Papaianina, Olena; Feofanov, Mikhail; Liu, Jia; Devarajulu, Mirunalini; Troyanov, Sergey; Maier, Sabine; Amsharov, Konstantin
Abstract Zig-zag nanographenes are promising candidates for the applications in organic electronics due to the electronic properties induced by their periphery. However, the synthetic access to these compounds remains virtually unexplored. There is a lack in efficient and mild strategies origins in the reduced stability, increased reactivity, and low solubility of these compounds. Herein we report a facile access to pristine zig-zag nanographenes, utilizing an acid-promoted intramolecular reductive cyclization of arylaldehydes, and demonstrate a three-step route to nanographenes constituted of angularly fused tetracenes or pentacenes. The mild conditions are scalable to gram quantities and give insoluble nanostructures in close to quantitative yields. The strategy allows the synthesis of elusive low bandgap nanographenes, with values as low as 1.62 eV. Compared to their linear homologues, the structures have an increased stability in the solid-state, even though computational analyses show distinct diradical character. The structures were confirmed by X–ray diffraction or scanning tunneling microscopy. Nanographenes with zig-zag peripheries are expected to have unique electronic properties, but their application in organic electronics has been curbed by their difficult synthesis. Here, the authors develop a facile route to zig-zag nanographenes based on a key dehydrative π-extension reaction.